Human-centred Innovations for Cognitive Ergonomics in Industry 4.0 - Torrecilla-García, Juan Antonio (My University, 2021)
The Cognitive Ergonomics present the increasing potential to enhance innovations within the Industry 4.0 paradigm. The emergent technologies of Industry 4.0 may become launching factors for design and development of specific solutions related to the cognitive risks and prevention management. The evaluation of the human factors in Industry 4.0 environments, makes feasible the establishment of mainframes of persons´ interaction with complex machine and digital systems. The human-centred innovations within the internal industry environments will also in-depth adaptations in firms’ business models or even the creation of new ones.
Keywords: Ergonomía - Congresos; Recursos humanos - Congresos; Cognitive Ergonomics, Industry 4.0; innovation, human-centred approach; occupational health and safety